Scars of COVID-19: A bibliometric analysis of post-COVID-19 fibrosis - Zhong, Han; Zhou, Yang; Mei, Shu-Ya; Tang, Ri; Feng, Jin-Hua; He, Zheng-Yu; Xu, Qiao-Yi; Xing, Shun-Peng (Frontiers in Public Health, 2022)
Background: The coronavirus disease 2019 (COVID-19) becomes a worldwide public health threat. Increasing evidences prove that COVID-19 induced acute injuries could be reversed by a couple of therapies. After that, post-COVID-19 fibrosis (PCF), a sequela of “Long Covid”, earns rapidly emerging concerns. Therefore, we aim to conduct a bibliometric analysis to explore the overall structure, hotspots and trend topics of PCF. Materials and Methods: A comprehensive search was performed in Web of Science core database to collect literature on PCF. Search syntax included COVID-19 relevant terms: “COVID 19”, “COVID-19 Virus Disease”, “2019 Novel Coronavirus Disease”, “SARS Coronavirus 2 Infection”; and fibrosis relevant terms: “Fibrosis”, “Fibroses”, “Cirrhosis”. Articles in English were included. Totally 1088 publications were enrolled. Searching results were subsequentially exported and collected for the bibliometric analysis. National, organizational, and individual level data were analyzed and visualized through biblioshiny package in R, VOSviewer software, CiteSpace software and Graphical Clustering Toolkit (gCLUTO) software, respectively. Results: The intrinsic structure and development in the field of PCF were investigated in present bibliometric analysis. The topmost keywords were “COVID-19” (occurrences, 636). The epidemiology, physiopathology, diagnosis and therapy of PCF were extensively studied. After this, based on dynamic analysis of keywords, hot topics sharply changed from “wuhan”, “inflammation”, and “cytokine storm” to “quality of life” and “infection” through burst detection. Similarly, co-cited references analysis showed that topics of references with most citation shift from “pulmonary pathology” (cluster 0) to “covid-19 vaccination” (cluster 6). Additionally, the overview of contributors, impact, collaboration was revealed. Summarily, USA stood out as the most prolific, influential, and collaborative country. The Udice French Research University, Imperial College London, and Harvard University, represented the largest volume of publications, citations, and H-index, respectively. Dana Albon was the most productive, cited and collaborative author. Journal of Cystic Fibrosis topped the list of prolific and influential journals. Conclusion: Outcomes gained from this study assisted professionals to better realize PCF and would guide future practices. Recent attention shifted to quality of life and COVID-19 vaccination which might be future research trends. Further international laboratory experiments was encouraged to promote exploration in the field of PCF.